STRATEGI PENGEMBANGAN USAHA WARUNG ZIPAU DI KAMPUNG CURUGSAWER KECAMATAN PANDEGLANG, KABUPATEN PANDEGLANG - Arif Rahman; Ria Estiana; Neni Nuraeni (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to determine the business development strategy of Warung Zipau in Pandeglang in order to survive in the culinary business that is getting tighter today. Warung Zipau is one of the MSMEs in Pandeglang that sells snacks such as fish balls with a distinctive taste and seblak with various filling variants. The method used in this study is using quantitative methods. The population used is buyers/customers who have made purchases at Warung Zipau in 2023, which is 7,160 customers with a sample of 99 people taken using a simple random sampling technique. This study uses SWOT analysis techniques, which compares external factors of opportunities and threats with internal factors of strengths and weaknesses using the internal strategy factor matrix or IFAS (Internal Factor Analysis Summary) and the external strategy factor matrix or EFAS (External Factor Analysis Summary). Warung Zipau based on internal strategies shows a strength score greater than a weakness score. While the external strategy shows an opportunity value score more than a threat value score. Reviewed through the calculation results in the IFAS and EFAS tables, it shows the results of the SO strategy which is in quadrant I, where this position supports an aggressive strategy, meaning that this position is a very profitable situation because Warung Zipau has a strong enough strength. To achieve business goals, the zipau stall business must develop future strategies by implementing a Growth Oriented Strategy.